Regular Class vs. Special Class: How Can They Differ in English Achievement and Technology Usage? - Inayatul Maula; Marisa Fran Lina (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Providing educational programs provides specific opportunities for better student progress. MTs Negeri 1 Boyolali offers two kinds of programs that can be chosen according to the wishes, abilities, and goals. The two programs are the regular class program and the special class program. These two programs can highlight their technology usage and English learning achievement, considering they come from different programs. Therefore, this study aims to find out whether there are differences in English learning achievement or not between the two programs. This study uses ,a mixed method; statistically collecting and analyzing the students' final semester tests results, and interviewing the teacher and students to clarify some data. Besides, an additional intervies investigates further technology usage during English learning. The data shows differences in English learning achievement and technology usage between students from regular and special class programs. The research is expected to be limited to find the differences between the two classes and to contribute ideas to all related education implementers. Ultimately, regular class students will have English skills that are not much different from students in special classes.